ANALYSIS AND CLASSIFICATION OF NUTRITIONAL, HUSBANDRY AND HEALTH RELATED PARAMETERS TO DEFINE SPECIALIST DAIRY FARMING - S. Yasar (Journal of Animal and Plant Sciences, 2010)
The level of specialist dairy farming in Burdur region of Turkey was determined by the analysis of nutritional, husbandry, breeding, health and product safety and quality parameters. A face-to-face questionnaire was conducted. The data obtained were classified and transformed to numerical values before statistical analysis. A multiple-response analysis was performed to define the classification of dairy farms into qualified, averaged and unqualified, which were established by algorithmic rules within each set of parameters. The results revealed that the level of specialist (qualified) dairy farms was only 47%, whereas 33% unqualified and 20% averaged. The nutritional expertise levels of farmers were not at a satisfactory level: 50% of farmers were qualified, 23% averaged and 27% were unqualified. The expertise level of farmers in feeds and feedings was dramatic: only 38% were qualified, 20% averaged and 42% unqualified. On the other hand, for animal husbandry, animal health and product safety criteria the farmers were not highly-skilled experts: 51% were qualified, 19% averaged and 30% unqualified.  In conclusion the specialist dairy farming system in Burdur accounts only 47% of the total. This figure is lower than an overall European figure of 83%. It showed that Turkish dairy farming is not convincing even some serious reforms were made. This suggests the need for intervention programmes to be undertaken in the region by the concerned public and private bodies.
Keywords: Nutrition; Husbandry; Specialist Dairy Farming; Decision-making indicators